The impact of persistent shocks and concave objective functions on collusive behavior - Johannes Paha (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
This paper provides a theoretic model for the analysis of cartel formation in an industry that is subject to profit shocks. The competitive or collusive conduct of a firm is determined by a decision maker who maximizes the present value of utility that accrues to him by earning a share of the firm's profit. The paper assumes that, first, factors like progressive taxation, shareholders' preference for smooth profits, or risk aversion may make the utility function of the decision maker rise concavely in the profits of the firm. Second, collusion causes the decision maker a dis-utility by violating legal and, thus, ethical or social norms. This disutility is independent from the level of profits. Concavity has adverse effects on collusion by making the decision maker value the additional utility from, first, establishing a new cartel, second, deviating from an existing cartel and, third, being punished for this deviation higher when the industry is in a bad state with low profits. Under these conditions, a negative profitability shock must be rather persistent to trigger cartel formation. Persistence prevents a newly formed cartel from falling apart quickly as the intense punishment in this state would also persist for a long time.
Keywords: D43; K21; L13; L41; M20; 330